We are what we mourn : the contemporary English-Canadian elegy - Uppal, Priscila (McGill-Queen's University Press, 2009)
Why are so many contemporary poets writing elegies? Given a century shaped by two world wars, vast population displacements, and shifting attitudes towards aging and death, is the elegy form adaptable to the changing needs of writers and audiences? In a sceptical age, where can consolation be found?